ANALISIS KUALITAS LAYANAN PADA PENYEDIA JASA TENAGA KERJA PT VARIA USAHA FABRIKASI - M. Vicky Hadi Siswanto; Moh. Agung Surianto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Service quality is an important aspect that needs to be considered in running a business, whether profit or non-profit oriented. When the quality of the service provided is very good, it will expedite the business process in the future. The purpose of this study was to analyze the quality of service to labor service providers at PT Varia Usaha Fabrication. The research method used was descriptive qualitative. The research results from the reliability aspect are quite good, it is known from statements from informants that more workers complete tasks on time than workers who do not complete work on time. In the aspect of responsiveness that is still not good, it is known from the informant's statement that the solution is not optimal, more customers provide solutions to problems that occur. The solution given is less effective in solving the problem. In the aspect of certainty or guarantee, it is still not well known from the informant's statement that the delay in fulfillment and not according to the labor specifications desired by the customer. the attention aspect was very well known from the informant's statement that communication was going well, easy to contact and the staff were friendly. In the tangible aspect, facilities and infrastructure are said to be very good according to the wishes of the customer. Completeness of work has been fulfilled so that customers are satisfied with the facilities and infrastructure that have been provided.